2020
DOI: 10.3390/microorganisms8020174
|View full text |Cite
|
Sign up to set email alerts
|

Stringent Selection of Knobby Plasmodium falciparum-Infected Erythrocytes during Cytoadhesion at Febrile Temperature

Abstract: Changes in the erythrocyte membrane induced by Plasmodium falciparum invasion allow cytoadhesion of infected erythrocytes (IEs) to the host endothelium, which can lead to severe complications. Binding to endothelial cell receptors (ECRs) is mainly mediated by members of the P. falciparum erythrocyte membrane protein 1 (PfEMP1) family, encoded by var genes. Malaria infection causes several common symptoms, with fever being the most apparent. In this study, the effects of febrile conditions on cytoadhesion of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Transcriptome profiling showed that IEs populations enriched for binding to HBEC-5i showed exclusive expression of var2csa and the HBEC-5i enriched population bind exclusively to CSA on the surface of HBEC-5i cells (Fig. S6A) 36 . A laminar flow system was used to imitate the hydrodynamic forces exerted on IEs in blood microvessels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome profiling showed that IEs populations enriched for binding to HBEC-5i showed exclusive expression of var2csa and the HBEC-5i enriched population bind exclusively to CSA on the surface of HBEC-5i cells (Fig. S6A) 36 . A laminar flow system was used to imitate the hydrodynamic forces exerted on IEs in blood microvessels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exclusive expression of var2csa was confirmed by qPCR and transcriptome analysis (Fig. S6A) 36 . To select IT4-IEs CSA with knobs (IT4-IEs CSA+K ), seven rounds of enrichment were performed at 40 °C (Fig.…”
Section: Binding Behaviors To Hbec-5i Cells Under Controlled Flow Andmentioning
confidence: 87%
See 1 more Smart Citation
“…EC proteins, such as CD51, ICAM-1 and VCAM-1, are presented on the surface, while others, such as CD31, CD36 and CD62E, are absent [ 72 ]. In addition, HBEC-5i cells carry chondroitin sulfate A (CSA) as a dominant molecule on its surface [ 73 ]. Nevertheless, HBEC-5i exhibits essential features of cerebral EC, including tight junction structures in particular [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The principal and most characterised group of VSA is P. falciparum erythrocyte membrane protein 1 (PfEMP-1). P. falciparum erythrocyte membrane protein 1 is encoded by var-genes and is reported to be dominantly expressed during the asexual stage of the parasite life cycle (Agudelo et al, 2014;Chan et al, 2014) and also associated with pathogenicity of the parasite (Dörpinghaus et al, 2020).…”
Section: Introductionmentioning
confidence: 99%